A new strategy to glue-seal κ-carrageenan film for packaging grease. (January 2023) - Chi, Wenrui; Liu, Wenhua; Xu, Shiyu; Zhan, Xianxu; Li, Jian; Wang, Lijuan
Abstract: In order to solve the problem that polysaccharide-based films cannot be heat-sealed into bags because their glass transition temperature is higher than the decomposition temperature. In this study, the anionic κ-carrageenan (κC) was transformed to a film to investigate the sealing procedure inevitable to produce bags. We propose a heat-free glue-sealing strategy that chitosan quaternary ammonium salt (CQAS) was used as a bio-glue to seal κ-carrageenan film (κCF) for food packaging by an electrostatic force, which were demonstrated by thermal stability and the light transmittance of the κC-CQAS. An increase in CQAS concentration resulted in an increase in sealing strength. After 75 d, the peroxide value (POV) of beef tallow packed in the glue-sealed κCF bags was 0.0713 g/100 g, which was lower than that of 0.1087 g/100 g in polyethylene (PE) bags. The mass of P-κC-CQAS decreased by 3.22% in soil after 21 d. This study provides a feasible, energy-saving and green strategy to produce anionic polysaccharide film bags to replace some of the plastic bags. Graphical abstract: Image 1 Highlights: CQAS was firstly used as a bio-glue to seal two κCF under a pressure. The obtained bags with good airtightness can extend the shelf life of grease food. The glue-sealed κ-carrageenan film is environmentally friendly.